'Gettin' on with these furriners': silent Western epics and American identity. (19th December 2018) - Hefner, Brooks E
Abstract: Although film critics were declaring the end of the Western in the early 1920s, the transition of the genre into epic modes in The Covered Wagon (Robert Cruze, 1923) and The Iron Horse (John Ford, 1924) reinvigorated the Western with a focus on large-scale entertainment and grand narratives about nation building. Both films debuted during an extreme period of US nativism, when politicians like Albert Johnson ushered in new legislation to the stop the 'foreign-born flood' that threatened to undermine 'the institutions which have made and preserved American liberties'. In this essay I argue that these Westerns – produced as the Johnson-Reed Immigration Act of 1924 was being debated and, ultimately, passed – respond to nativist, anti-immigrant ideology in radically different ways. In so doing, each of these two films works to mould the Western genre itself around new epic forms, layering melodramatic individual narratives over broader national history. The oscillation between narrative foreground and background is mirrored by a system of visual information that reinforces the films' notion of American history and identity. In both cases, contemporary reviewers and audiences latched onto the complex politics of these pioneering Western epics. While The Covered Wagon emphasized a homogeneous Anglo-Saxon 'blood of the pioneers', The Iron Horse presented a multiethnic vision of American labour in service of national reconstruction. Rooted in contemporaneous 1920s debates about American identity, American labour, nativist politics, and immigration, these competing perspectives demonstrate both the flexibility of the Western genre and its ability to offer forms of cultural resistance.